2022
DOI: 10.1371/journal.pone.0262597
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial resistance pattern of Clostridium difficile among hospitalized diarrheal patients: A systematic review and meta-analysis

Abstract: Background Clostridium difficile is the leading cause of infectious diarrhea that develops in patients after hospitalization during antibiotic administration. It has also become a big issue in community-acquired diarrhea. The emergence of hypervirulent strains of C. difficile poses a major problem in hospital-associated diarrhea outbreaks and it is difficult to treat. The antimicrobial resistance in C. difficile has worsened due to the inappropriate use of broad-spectrum antibiotics including cephalosporins, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 51 publications
0
13
0
1
Order By: Relevance
“…The antibiotics used to treat C. difficile splenic abscesses were intravenous vancomycin, metro-nidazole, and penicillin, although antimicrobial susceptibilities of C. difficile were not available except for our case ( Tables 1 , 2 ). The systematic review and meta-analysis on C. difficile infection among hospitalized diarrheal patients showed that the resistance to metronidazole and vancomycin was low compared to other drugs, including clindamycin [ 25 ]. A single-center retrospective study on ECDI demonstrated that all isolates (100%) were susceptible to metronidazole and piperacillin-tazobactam, while 63% and 9% of isolates were susceptible to ertapenem and clindamycin, respectively [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antibiotics used to treat C. difficile splenic abscesses were intravenous vancomycin, metro-nidazole, and penicillin, although antimicrobial susceptibilities of C. difficile were not available except for our case ( Tables 1 , 2 ). The systematic review and meta-analysis on C. difficile infection among hospitalized diarrheal patients showed that the resistance to metronidazole and vancomycin was low compared to other drugs, including clindamycin [ 25 ]. A single-center retrospective study on ECDI demonstrated that all isolates (100%) were susceptible to metronidazole and piperacillin-tazobactam, while 63% and 9% of isolates were susceptible to ertapenem and clindamycin, respectively [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current antibiotic therapies, including treatments with vancomycin and fidaxomicin, may alleviate the disease (Khanna et al, 2016;Cho et al, 2020). However, the emergence of antibiotic-resistant C. difficile strains and the risk of recurrent CDI (rCDI) after antibiotic treatment are major public health concerns (Cornely et al, 2012;Sholeh et al, 2020;Tsigrelis, 2020;Dilnessa et al, 2022). Although fecal microbiota transplantation is effective in treating rCDI, the efficacy, safety, and stability of this method need to be considered and discussed (Weingarden et al, 2015;Colleen et al, 2016;Youngster et al, 2016;Chiu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Tis bacterium came into the limelight in 1978 as the leading cause of diarrhea caused by antibiotics, called "Antibiotic-Associated Diarrhea." Also, this disease was introduced as the prime cause of pseudomembranous colitis and patient mortalities, particularly in the elderly [6]. Toxin A (tcd A) and toxin B (tcdB) are two virulence factors associated with C. difcile infection, which are enterotoxin and cytotoxin, respectively [7].…”
Section: Introductionmentioning
confidence: 99%